ANALISIS PENGARUH INFLASI, SUKU BUNGA DAN NILAI TUKAR TERHADAP PROFITABILITAS PERBANKAN - Puguh Roni Prastowo; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT This study aims to determine the effect of Inflation, Interest rates, and exchange rate to predict a profitability. The population in this study are all banking companies listed on Indonesia Stock Exchange period 2014-2016. Sample in this study using purposive sampling technique amounted to 34 companies. The analysis was done by using secondary data and multiple regression analysis method. The results of this study indicate that inflation partially positive and insignificant influence on changes in profitability with value (sig. 0,947), Interest rate partially have a negative and insignificant effect on changes in profitability with value (sig. 0,661), and Exchange rate partially have a negative and insignificant effect on changes in profitability with value (sig. 0,597). Keywords: Systematic Risk, Inflation, Interest rate, Exchange Rate, Profitability